Almost, but not quite bored in Pula : an anthropological study of the tapija phenomenon in Northwest Croatia - Matošević, Andrea, 1979-; Hodges, Andrew, (Social anthropologist) (New York : Berghahn Books, 2021)
"Based on interviews and fieldwork conducted among residents of Pula, a coastal city in Northwestern Croatia, this study explores various aspects of a local feeling of boredom. This is mirrored in the term tapija, a word of Turkish origin describing a property deed, and in Pula's urban slang it has morphed from its original sense describing a set of affective states into one of lameness, loneliness, unwillingness, and irony. Combining lively conversations with a significant bibliography of the topic, the result is a compelling local anthropological study of boredom in a wider historical and global context"--
On tapija : an ethnography of the city's imponderables -- Boredom, or the city yawns -- On dominant articulations and reaches of tapija.
Originally published: Matošević, Andrea. Doći u Pulu, dospjeti u tapiju : etno-filozofska studija lokalnog fenomena. Durieux and Institut za etnologiju i folkloristiku, 2019.
Sisältää bibliografisia viitteitä ja hakemiston.
Keywords: Boredom -- Croatia -- Pula; Sociology, Urban -- Croatia -- Pula; ikävystyminen; ilmapiiri; paikalliskulttuuri; pikkukaupungit; Pula (Croatia) -- Social life and customs; Kroatia